Students' Perceptions of Gemini AI as a Learning Assistant in Writing Class of Fourth Semester of STKIP Muhammadiyah Pagaralam - Ayu, Mellisya Sekar; Fitrilia, Ise; Wahyuni, Sri (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2026)
This study investigates students’ perceptions of Gemini AI as a learning assistant in the writing class of fourth-semester students at STKIP Muhammadiyah Pagaralam. Using a descriptive qualitative approach, data were collected through open-ended questionnaires distributed to 30 fourth-semester students from Class A (17 students) and Class B (13 students) selected via purposive sampling. The data were analyzed using thematic analysis following Braun and Clarke’s framework. The findings reveal that students hold predominantly positive perceptions of Gemini AI, perceiving it as a comprehensive writing support tool that assists in idea generation, writing structure organization, writing quality improvement, time efficiency, vocabulary development, and overcoming writing difficulties. Students also reported increased confidence and motivation after using Gemini AI. However, challenges were identified, including concerns about output accuracy, potential dependency on AI, and issues related to plagiarism. Overall, Gemini AI functions as a multifaceted learning assistant that positively influences both the technical and emotional dimensions of students’ writing experiences, although balanced and critical use is strongly recommended.